Elena Cotta Ramusino, Elizabeth Bowen’s Other Writing. A Study of Her Non-Fictional Prose - Elena Ogliari (Altre Modernità, 2018)
Elena Cotta Ramusino, Elizabeth Bowen’s Other Writing. A Study of Her Non-Fictional Prose